CT and MRI Features of Chondrosarcoma in the Mastoid Involving the Facial Nerve in Comparison to Facial Nerve Schwannoma - Liu, Jun-hua; Qi, Meng; Sha, Yan; Zhang, Fang (Current Medical Imaging, 2024)
Background Chondrosarcoma in the mastoid is extremely rare, and it is easily misdiagnosed as a facial nerve schwannoma. Objective To identify and compare computed tomography (CT) and magnetic resonance imaging (MRI) features of chondrosarcoma in the mastoid involving the facial nerve, including diffusion-weighted MRI characteristics, with those of facial nerve schwannoma. Methods CT and MRI features of 11 chondrosarcomas in the mastoid involving the facial nerve and 15 facial nerve schwannomas, confirmed by histopathology, were retrospectively reviewed. The tumor location, size, morphological features, bone change, calcification, signal intensity, texture, enhancement characteristics, the extent of lesions, and apparent diffusion coefficients (ADCs) were evaluated. Results On CT imaging, calcification could be found in 81.8% of chondrosarcomas (9/11) and 33.3% of facial nerve schwannomas (5/15). Chondrosarcoma in the mastoid appeared significantly hyperintense on T2-weighted images (T2WI) with low signal intensity septa in eight patients (72.7%, 8/11). After contrast, all chondrosarcomas showed inhomogeneous enhancement, and septal and peripheral enhancement could be found in six cases (54.5%, 6/11). Facial nerve schwannoma demonstrated inhomogeneous hyperintensity on T2WI in 12 cases (80%, 12/15), with obvious hyperintense cystic changes in seven cases. There were significant differences in calcification (P=0.014), T2 signal intensity (P=0.006), and septal and peripheral enhancement (P=0.001) between chondrosarcomas and facial nerve schwannomas. The ADCs of chondrosarcoma were significantly higher than those of facial nerve schwannomas (P<0.001). Conclusion CT and MRI with ADCs had the potential to improve the diagnostic accuracy of chondrosarcoma in the mastoid involving the facial nerve.
Keywords: Diffusion-weighted imaging